2022
DOI: 10.1177/09636625221093194
|View full text |Cite
|
Sign up to set email alerts
|

Guidance in the chaos: Effects of science communication by virologists during the COVID-19 crisis in Germany and the role of parasocial phenomena

Abstract: During the COVID-19 pandemic, virologists gained a prominent role in traditional and social media in Germany; several participated in regular podcasts. Using a two-wave survey ( n = 696/361 at Time 1/2), we explore which impact the strong media presence of virologists had on media users and what role parasocial phenomena (asymmetric interactions and relationships with virologists) played. People who favored a specific virologist scored higher on various cognitive, affective, and behavioral outcomes. Exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 40 publications
2
15
0
Order By: Relevance
“…Already one decade ago, Birch and Weitkamp (2010) showed that audiences view podcasts as valuable sources of scientific information. A high frequency of exposure to health-related podcasts showed increased strength of parasocial phenomena, which mediated between frequency of listening to podcasts and cognitive (e.g., knowledge), affective (e.g., solace) as well as behavioral (e.g., engagement) outcomes (Utz et al, 2022). Hence, Utz et al (2022) demonstrated that the development of social bonds with science communicators matters, and longer conversational formats comprise a value for science communication.…”
Section: Podcasts and User Engagementmentioning
confidence: 99%
See 4 more Smart Citations
“…Already one decade ago, Birch and Weitkamp (2010) showed that audiences view podcasts as valuable sources of scientific information. A high frequency of exposure to health-related podcasts showed increased strength of parasocial phenomena, which mediated between frequency of listening to podcasts and cognitive (e.g., knowledge), affective (e.g., solace) as well as behavioral (e.g., engagement) outcomes (Utz et al, 2022). Hence, Utz et al (2022) demonstrated that the development of social bonds with science communicators matters, and longer conversational formats comprise a value for science communication.…”
Section: Podcasts and User Engagementmentioning
confidence: 99%
“…Highly personalized science communication approaches may engage the audience even in a one-way communication setting: Utz et al (2022) demonstrated that parasocial phenomena, i.e., the perceived familiarity and asymmetrical interaction with a science communicator, mediates several cognitive, affective, and behavioral variables like content knowledge, solace, and engagement.…”
Section: Health Communication During a Pandemicmentioning
confidence: 99%
See 3 more Smart Citations